Art Education as A Means of Developing Creativity in Choir Training - Narindra Qonita*; Trisakti Trisakti; Retnayu Prasetyanti Sekti (Riwayat: Educational Journal of History and Humanities, 2023)
Art education has a very large influence on the development of student creativity. In choir training, teachers must also have creativity in conveying material at training so that they can produce good quality choral groups. The purpose of writing this article is to explain the role of artistic creativity, the implementation of music and choir learning in schools, and choral training strategies as a means of developing creativity. This research uses a qualitative approach with a descriptive conceptual analysis method. This study uses a conceptual analysis method that examines various literature related to the research objectives. Data analysis techniques carried out in this study were data reduction, data presentation, and data analysis. The results of data analysis show that music arts education and choir training can be a means of developing creativity for performers, both students and teachers. Choir training can help students be creative in expressing the song that is being sung, therefore it is necessary for teachers who have the knowledge and ability to work on strategies for learning choral art to develop students' creativity.